2006
DOI: 10.1093/sp/jxj005
|View full text |Cite
|
Sign up to set email alerts
|

Policy, Preferences, and Patriarchy: The Division of Domestic Labor in East Germany, West Germany, and the United States

Abstract: Individual agency observed in the gendered division of labor is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 57 publications
1
48
0
6
Order By: Relevance
“…Countries vary considering the extent to which work-family policies reinforce gendered responsibilities for unpaid and paid work (e.g., Cooke 2006;Korpi 2000;Orloff 1993). Previous studies have shown that social support from the state influences mothers' labour market participation and attachment (see Allen et al 2013;Misra, Budig, and Boeckman 2011;Keck and Saraceno 2013).…”
Section: Work-family Policies and Gender Norms In Different Welfare Smentioning
confidence: 99%
“…Countries vary considering the extent to which work-family policies reinforce gendered responsibilities for unpaid and paid work (e.g., Cooke 2006;Korpi 2000;Orloff 1993). Previous studies have shown that social support from the state influences mothers' labour market participation and attachment (see Allen et al 2013;Misra, Budig, and Boeckman 2011;Keck and Saraceno 2013).…”
Section: Work-family Policies and Gender Norms In Different Welfare Smentioning
confidence: 99%
“…While many studies note that gender norms are persistent and continue to dictate household's earning strategies, some comparative researchers have argued and empirically shown that there are important differences in gendered behaviour and attitudes by nationalinstitutional context (Pfau-Effinger 1998;Cooke 2006;O'Reilly et al, 2014). Their evidence suggests that policy and history structure the gender contract between men and women and that they are, therefore, open to change (O'Reilly et al, 2014).…”
Section: How Might Family Dynamics Influence Women's Market Outcomes?mentioning
confidence: 99%
“…In 2012, 22 % of children under three years attended formal day-care facilities in West Germany compared to 46 % in East Germany (Statistisches Bundesamt 2012). Mothers in East Germany remain more accepting of full-time employment and of using formal child care for young children than those in West Germany (Cooke, 2006;Raz-Yurovich, 2012). As a result, the employment decisions of West German mothers with a youngest child under the age of three may depend more strongly on whether they feel comfortable with the quality of care offered in local ECEC centers than of mothers in East Germany (Hypothesis 3a).…”
Section: Institutional Moderators: Day-care Availability and Work-carmentioning
confidence: 99%
“…West Germany has had a long history of extended maternal leaves after childbirth and policies supporting the male breadwinner family model, whereas in East Germany mothers' labor force participation traditionally has been encouraged via publicly provided day care and other family polices (Rosenfeld et al, 2004). These historical differences are still reflected in more conservative attitudes of parents towards maternal employment and using formal day-care for young children in West Germany compared to East Germany and to the US (Cooke, 2006;RazYurovich, 2012;Rosenfeld et al, 2004).…”
mentioning
confidence: 99%